The Role of the Principal in Improving the Professionalism of Islamic Education Teachers at MA Pondok Putri 1 Al-Amien Prenduan - Najmi Faza; Rohmaniatun Fitria (Penerbit Hellow Pustaka, 2026)
The quality of an educational institution depends on the principal as the leader of the institution. Therefore, the principal has the duty to provide guidance and supervision to every teacher who is in charge in his or her respective field of study. To carry out his duties as a coach and supervisor in developing teacher professionalism and improving the quality of effective learning, a school principal must have the ability and understanding of the principal's competence well. find out the role of the principal in improving the professionalism of PAI teachers at MA Female Boarding 1 Al-Amien Prenduan and to find out the blocking and inhibiting factors that improve the professionalism of PAI teachers at MA Female Boarding 1 Al-Amien Prenduan. This research is a descriptive qualitative research with data collection techniques carried out using the Triangulation method. Data collected by observation, interviews, and documentation. The subjects in this study are homeroom teachers as social support providers, as well as new students as recipients of social support.The conclusion of this study is that with the support of the principal and the teacher himself, it will accelerate the improvement of teacher professionalism. The supporting factors for school principals in improving the professionalism of PAI teachers are by giving appreciation to teachers, providing good examples, supporting facilities and infrastructure, and fostering cooperation between teachers. Meanwhile, the inhibiting factors of school principals are that students do not listen to teachers during learning and internal factors such as family or teacher background.